Y-cracking in continuously reinforced concrete pavements - Momeni, Amir Farid (Kansas State University, 2013)
When transverse cracks meander there is a high possibility for transverse cracks to meet at a point and connect to another transverse crack, creating a Y-crack. Y-cracks have been blamed for being the origin of punchouts and spallings in CRCPs. When the direction of maximum principal stress changes, it could cause a change in the crack direction, potentially forming a Y-crack. Finite Element Models (FEMs) were run to model the change in principal stress direction based on design and construction conditions. The finite element model of CRCP using typical Oklahoma CRCP pavement conditions and design was assembled. The model included the concrete pavement, asphalt concrete subbase, and soil subgrade. The effect of areas of changed friction on the direction of principal stress was simulated by considering a patch at the pavement-subbase interaction. Investigated factors related to this patch were location of patch, friction between patch and subbase, and patch size. Patches were placed at two different locations in the pavement: a patch at the corner of the pavement and a patch at the longitudinal edge between pavement ends. A change in the friction at the corner had a large effect on the stress magnitude and direction of principal stress, while a patch in the middle did not significantly change the stress state. Also, patch size had a noticeable effect on stress magnitude when the patch was at the corner. Another model was developed to understand the effect of jointed shoulder on direction of maximum principal stress. Analysis of this model showed that the stresses were not symmetric and changed along the width of the pavement. This meandering pattern shows a high potential for Y-cracking. Also, several finite element models were run to understand the effects of different shrinkage between mainline and shoulder. In order to simulate the effects of the differential drying shrinkage between the hardened mainline concrete and the newly cast shoulder, different temperature changes were applied on the mainline and shoulder. For these models, the orientation of the maximum principal stress was not significantly changed from different amounts of temperature decreases between mainline and shoulder. Also, effect of different longitudinal steel percentages was investigated by comparing two finite element models with different steel percentage. The model with higher steel percentage (0.7%) indicated more variation in stress, potentially leading to more crack direction diverging.
Keywords: Y-cracking; Continuously reinforced concrete pavement; Civil Engineering (0543); Materials Science (0794)